Audience analysis - McQuail, Denis (Sage Publications, 1997)
In Audience Analysis, author Denis McQuail provides a coherent and succinct account of the concept "media audience" in terms of its history and its place in present-day media theory and research. He describes and explains the main types of audience, alternative theories about the audience, and the main traditions and fields of audience research.